Effect of the trap/divergent flow channel on the performance of open-cathode proton exchange membrane fuel cells - Minyuan Du; Yi Liu; Jilin Lei; Shiyao Zhao; Hu Peng; Shuchao He; Rui Mo (Results in Engineering)
Enhancing the lateral velocity of gas reaching the catalytic layer is a common strategy to optimize the performance of proton exchange membrane fuel cells (PEMFCs). Utilizing trap configurations and divergent flow channels can effectively enhance the molar concentration of oxygen in the cathode catalytic layer without impacting the pressure drop within the cathode flow channel. This study explores PEMFC models featuring various trap configurations, varying in factors such as the quantity and length of traps employed. The findings suggest that augmenting the number of traps bolsters the mass transfer of cathode reactants and thus fosters enhanced uniformity of reactants throughout the fuel cell. Consequently, the flow resistance of the channels decreases, resulting in an augmented power density of the fuel cell. Optimal trap performance is observed with the incorporation of six pairs of traps. Compared to the initial divergent channel design, the power output is increased by 9.86%. Moreover, setting up multiple traps within the channel, while maintaining a constant current density across the membrane, enhances the uniformity of cathode reaction products along the catalytic layer surface of the cell. Notably, the sixth trap increased the reactant concentration by 11% (compared to n=0) and 6% (compared to n=5), respectively, confirming that optimization of the number of traps leads to significant improvements. The combined enhancements decrease flow resistance by 12% and elevate cell efficiency by 8%. This work provides fundamental insights for designing trapped divergent cathode flow fields.